Strategi Komunikasi Politik Digital dalam Membangun Citra Publik: Analisis Konten YouTube Dedi Mulyadi - Adam, Wahyu; Setiadarma , Dani (Jurnal Ilmu Sosial dan Humaniora, 2026)
This research is motivated by the public communication phenomenon carried out by the Governor of West Java, Dedi Mulyadi, through his YouTube channel, which has received widespread attention from the public, especially in West Java and netizens in Indonesia. Digital media provides a space for public figures to convey messages directly to the public through narrative and interactive audio-visual content. This study aims to analyze the communication strategies used in building a positive image through the YouTube platform. This study uses a qualitative approach with content analysis methods and in-depth interviews with six informants consisting of internal and external informants. The data obtained are analyzed using thematic analysis techniques to identify patterns of communication strategies and the image built in the eyes of the public. The results show that Dedi Mulyadi’s communication strategies are diverse, including the perception of a humanist leader, a personal branding approach, and a populist communication style. The mapping of the formed image includes a leader who is close to the people, transparent, and humanistic, as well as a planned emotional personal branding with symbolic humanity. Dedi Mulyadi’s use of YouTube is an effective communication strategy in building public trust. The success of this strategy is also reflected in digital indicators such as the number of subscribers, likes, comments, and content sharing. Furthermore, the effectiveness of this communication strategy is due to the narrative and humanistic speaking style used, which were appropriately received, especially by informants from West Java Province. Despite challenges such as the potential for misinformation and negative comments, message consistency, transparency, and open responses are key to maintaining a positive image and strengthening the emotional connection between leaders and the public.